Pengaruh Partisipasi Anggaran terhadap Senjangan Anggaran dengan Kemampuan Pengawas Internal sebagai Variabel Pemoderasi - Magung, Febryanto Hardianus; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p24, 2018)
This study aims to provide information relevant to internal internals to moderate fund accounts in budgetary slack. The population in this research is the structural officer in OPD area of Denpasar Transportation Government Department, which consist of Structural Official of Echelon II - IV. Sampling technique used in this research is Nonprobability Sampling, especially Saturated Samples. The sample used 28 people who used survey method data as questionnaire. Data is processed using the Statistical Package for Social Science (SPSS) program for windows for the hypotheses that have been formulated. Result of validity test and reliability of acceptable result. The result of Moderated Regression Analysis (MRA) analysis from budget fund to internal management as moderator variable, found that internal supervisor ability can influence budget and budget.  Keywords: internal auditors, participation, slack, budgetary